Intercepting Stimulus-Organism-Response Model, Theory of Planned Behavior and Theory of Expectancy Confirmation in the Study of Smartphone Consumer Behavior: A Thai University Student Perspective - Tan, Chai Ching (Asia Pacific Journal of Religions and Cultures, 2019)
This research targets two very important objectives. First, it exploits the similarity structure of the theory of planned behavior, expectancy confirmation theory and the stimulus-organism-response (S-O-R) model, in broadening the social-psychological context in the use of the S-O-R model, and which renders the model being capable of embracing a broad-based, strategically competitive structure of business competition that centralizes on marketing mix strategy, customer value proposition and customer attitude. Second, through both explorative and explanatory efforts of an action learning and PDCA (Plan, Do, Check, Act) approach to business research, a S-O-R model, that is capable of explaining of the smartphone consumer behaviors, is corroborated, which highlights significant roles played by business model structure of variables, and organism variables constituting brand trust, customer satisfaction and brand equity, in explaining the variance of customer loyalty. Customer switching cost, which is a direct result of perceived customer value, is also shown to influence brand trust, significantly.